2023
DOI: 10.1111/bph.16068
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of oxidative stress by apocynin attenuated chronic obstructive pulmonary disease progression and vascular injury by cigarette smoke exposure

Abstract: Background and Purpose Cardiovascular disease affects up to half of the patients with chronic obstructive pulmonary disease (COPD), exerting deleterious impact on health outcomes and survivability. Vascular endothelial dysfunction marks the onset of cardiovascular disease. The present study examined the effect of a potent NADPH Oxidase (NOX) inhibitor and free‐radical scavenger, apocynin, on COPD‐related cardiovascular disease. Experimental Approach Male BALB/c mice were exposed to either room air (Sham) or ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Xinjing et al reported that NOX 1, 4, and 5 were detected at various sites such as lung epithelial cells, vascular endothelial cells, and macrophages, and NOX2 was mainly detected in lung macrophages and neutrophils [ 214 ]. Stanley et al also reported that the NOX inhibitor apocynin inhibited lung inflammation and vascular injury caused by oxidative stress in the CS-induced mouse model [ 215 ]. In addition, expression of NOX in COPD has been reported in several studies [ 216 , 217 , 218 ].…”
Section: Cs-induced Lung and Other Diseasesmentioning
confidence: 99%
“…Xinjing et al reported that NOX 1, 4, and 5 were detected at various sites such as lung epithelial cells, vascular endothelial cells, and macrophages, and NOX2 was mainly detected in lung macrophages and neutrophils [ 214 ]. Stanley et al also reported that the NOX inhibitor apocynin inhibited lung inflammation and vascular injury caused by oxidative stress in the CS-induced mouse model [ 215 ]. In addition, expression of NOX in COPD has been reported in several studies [ 216 , 217 , 218 ].…”
Section: Cs-induced Lung and Other Diseasesmentioning
confidence: 99%